Evaluation of Parking Space Needs for Karya Bhakti Pratiwi Hospital - Adi, Muhamad; Rulhendri, Rulhendri; Alimuddin, Alimuddin (ASTONJADRO, 2026)
Karya Bhakti Pratiwi Hospital is located in the Dramaga area of ​​Bogor Regency. This hospital is owned by an individual, namely PT Karya Bhakti Pratiwi, built on 4,715 square meters of land, Karya Bhakti Pratiwi Hospital has obtained an operational permit for Health services since 2012 (Regent's Decree Number 445/154/Kpts/Per-UU/2012). With the increasing population density of West Bogor, of course, visits to the Hospital will also increase, therefore it is necessary to have supporting facilities such as adequate parking areas so that visitors feel safe and comfortable when parking their vehicles. In this study using the SRP characteristic method (Volume, Accumulation, Duration, Over Turn Over, Index), in this study is the Evaluation of Parking Space Needs. Data collection was carried out using a survey method with a time of 10 hours and running for seven days with the aspects taken being data on vehicle entry and exit times to determine parking characteristics. The results of this study indicate that the need for parking space cannot accommodate motorcycles, an area of ​​310m2 has a parking capacity of 120 SRP. In this analysis study, the results of the largest accumulated static capacity were 147 vehicles with an average parking duration of 09:48 hours on the peak day, namely Wednesday, February 11, 2025. During the seven days of the survey, it was found that the maximum parking volume was 274 vehicles with a maximum vehicle parking accumulation of 220 vehicles which occurred on Thursday, February 13, 2025. The highest motorcycle parking turnover at Cilebut Station reached 220.97%, this shows that motorcycle parking performance is quite high. The capacity of motorcycle parking space at Karya Bhakti Pratiwi Hospital cannot meet existing parking needs. This is indicated by looking at the parking index exceeding 100%.